2005
DOI: 10.1007/s10733-005-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

A Diffusion-Kinetic Model for Radiation-Chemical Transformations of Oxalic Acid and Oxalate Ions in Aqueous Solutions

Abstract: A diffusion-kinetic model for the radiation-chemical degradation of oxalic acid and oxalates in aqueous solutions was developed. The model adequately describes published data on the formation of H 2 , H 2 O 2 , and CO 2 over wide ranges of acid concentrations and pH values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Radiolytic processes, especially those associated with the formation of excited molecules, dissociative capture of radicals, and oxidation, can lead to the formation of cleavage products of C–C bonds as well as bonds between a carbon and a heteroatom. Under anaerobic conditions, radiolysis eliminates gaseous fragmentation products such as H 2 , CO 2 , CH 4 , N 2 , etc. , Under aerobic conditions, organic pollutants can undergo sequential cleavages, leading to their complete conversion to CO 2 and H 2 O or, in the presence of heteroatoms, to oxides of the corresponding elements (SI, section S1). Such a process is called mineralization.…”
Section: Combined Application Of Treatment Methodsmentioning
confidence: 99%
“…Radiolytic processes, especially those associated with the formation of excited molecules, dissociative capture of radicals, and oxidation, can lead to the formation of cleavage products of C–C bonds as well as bonds between a carbon and a heteroatom. Under anaerobic conditions, radiolysis eliminates gaseous fragmentation products such as H 2 , CO 2 , CH 4 , N 2 , etc. , Under aerobic conditions, organic pollutants can undergo sequential cleavages, leading to their complete conversion to CO 2 and H 2 O or, in the presence of heteroatoms, to oxides of the corresponding elements (SI, section S1). Such a process is called mineralization.…”
Section: Combined Application Of Treatment Methodsmentioning
confidence: 99%
“…The absence of unsaturated bonds in them affects this. However, in this case, the formation of formate and oxalate is fixed also [ 113 , 114 , 115 , 116 , 117 , 118 , 119 ]. These low molecular weight carboxylate compounds, along with H 2 , can play an important role in maintaining subsurface lithoautotrophic microbial ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of radiation-induced synthesis is also supported by computer simulation of the radiolysis of simple organic compounds—oxalic and acetic acids. It was shown that the decomposition of oxalic acid gives tartaric, tartronic, glyoxylic, and many other organic acids [ 113 , 114 ], while the decomposition of acetic acids gives glycolic and glyoxalic acids, formaldehyde, and other products [ 115 ]. It can be stated, with sufficient certainty, that the radiation-induced chemical transformations of aqueous solutions of CO, CH 4 , HCHO, HCN, and other simple organic compounds makes it possible, in principle, to synthesize an almost infinite set of organic products.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, detailed knowledge of the processes interlining the radiolysis of oxalic acid which is one of the components of liquid radioactive waste remains still of interest. Radiation chemical degradation of oxalic acid produces long row of organic acids and gaseous products like CO 2 and H 2 [2]. Radiolysis of aqueous solutions of oxalic acid has been previously investigated [2][3][4], but they cover either the initial or late stages of oxalic acid degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation chemical degradation of oxalic acid produces long row of organic acids and gaseous products like CO 2 and H 2 [2]. Radiolysis of aqueous solutions of oxalic acid has been previously investigated [2][3][4], but they cover either the initial or late stages of oxalic acid degradation. However, there is no systematic investigation covering wide range of absorbed irradiation dose, which makes it difficult for proper understanding the mechanism of radiolysis of aqueous oxalic acid solution and consequently the mechanism of complete phenol degradation into CO 2 and H 2 O as well as utilization and safe storage of liquid radioactive waste.…”
Section: Introductionmentioning
confidence: 99%